PERBANDINGAN MORFOLOGI BAHASA TERNATE DAN BAHASA INDONESIA (ANALISIS KONTRASTIF) - Muhammad Ahmad (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2019)
This study aims to compare the affixation process of Ternate language forming with Indonesian. Affixes described along with affixation process forming. The method used in this study is descriptive. Data sources are Ternate language textbooks by the Regional Language Center of Ternate and Indonesian Language books. The all derived verbs in Ternate and Indonesian language books. Data collection with reading and note-taking techniques. The results showed that the affixes form derived verbs consist of prefixes, suffixes, and confixes. Prefixes in Ternate are ma and maku which are compatible with the Indonesian prefixes me and berand form active verbs. The suffix si in Ternate corresponds to the suffix kanin Indonesian and forms the active derivative verb. The Ternate language confix masi and fosi in line with Indonesian me-kanis a form of active derivative verbs. Simaku confix in Ternate matches the confession of memper-kan in Indonesian and is an active derivative of verbs.